A Monolithic Electrochemical Micro Seismic Sensor Capable of Monitoring Three-Dimensional Vibrations - Lianhong Chen; Zhenyuan Sun; Guanglei Li; Deyong Chen; Junbo Wang; Jian Chen (Sensors, 2018)
A monolithic electrochemical micro seismic sensor capable of monitoring three-axial vibrations was proposed in this paper. The proposed micro sensor mainly consisted of four sensing units interconnected within flow channels and by interpreting the voltage outputs of the sensing units, vibrations with arbitrary directions can be quantified. The proposed seismic sensors are fabricated based on MEMS technologies and characterized, which produced sensitivities along x, y, and z axes as 2473.2 ± 184.5 V/(m/s), 2261.7 ± 119.6 V/(m/s), and 3480.7 ± 417.2 V/(m/s) at 30 Hz. In addition, the vibrations in x-y, x-z, and y-z planes were applied to the developed seismic sensors, leading to comparable monitoring results after decoupling calculations with the input velocities. Furthermore, the results have shown its feasibilities for seismic data recording.